2009
DOI: 10.1007/s11655-009-0337-z
|View full text |Cite
|
Sign up to set email alerts
|

Study on the changes of thrombosis-associated factors in patients with coronary heart disease of turbidity-phlegm blocking syndrome

Abstract: The TPB: syndrome in CHD patients was closely related to the blood coagulation-fibrinolytic system; they might be in pre-thrombosis state, and the plasma levels of vWF, D-dimer, and Fg could be taken as the objective indices for thrombosis differentiation of TPB syndrome in CHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Wang et al found that the levels of three indices (Von Willebrand factor, D-dimer, and fibrinogen) increased in CHD patients and were higher in phlegm syndrome patients than in non-phlegm syndrome patients ( P < 0.05). They thought these three markers could be taken as the markers for differentiating phlegm syndrome in CHD patients [ 16 ]. Sun et al discovered a significant decrease in E-cad/intercellular adhesion molecule-1 expression in phlegm syndrome patients with gastric carcinoma compared to those with the deficiency in both qi and blood and the deficiency-cold of stomach and spleen syndromes [ 17 ].…”
Section: Relation Between Phlegm Syndrome and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al found that the levels of three indices (Von Willebrand factor, D-dimer, and fibrinogen) increased in CHD patients and were higher in phlegm syndrome patients than in non-phlegm syndrome patients ( P < 0.05). They thought these three markers could be taken as the markers for differentiating phlegm syndrome in CHD patients [ 16 ]. Sun et al discovered a significant decrease in E-cad/intercellular adhesion molecule-1 expression in phlegm syndrome patients with gastric carcinoma compared to those with the deficiency in both qi and blood and the deficiency-cold of stomach and spleen syndromes [ 17 ].…”
Section: Relation Between Phlegm Syndrome and Diseasesmentioning
confidence: 99%
“…Phlegm syndrome was found to have several synonyms in many papers. For instance, phlegm syndrome could be named “phlegm congealment type” [ 15 ], “phlegm-dampness syndrome” [ 13 ], or “turbidity-phlegm blocking syndrome” [ 16 ] in different studies. These unstandardized syndrome names hindered the understanding implication of phlegm syndrome to some extent.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…And the main strategies include: (1) conducting the metabonomic and proteomic research (Shi et al, 2014b ; Zou et al, 2014 ; Jiang et al, 2015 ; Sun et al, 2015 ); (2) constructing MiRNA-target network (Liao et al, 2016 ; Liu et al, 2017 ); (3) integrating the classical formulas or herb pair (Chen et al, 2016 ; Xu et al, 2016 ; Zhou et al, 2016 ; Yue et al, 2017 ); (4) analyzing compound–nature pairs from TCM via chemical space visualizations (Liang et al, 2013 ; Fu et al, 2017 ); (5) using compound-target-disease associations to reconstruct the biologically-meaningful networks based on systems pharmacology (Zhou and Wang, 2014 ). Moreover, in recent years, a growing number of studies have focused on the biological mechanisms underlying BS with IHD (Mao et al, 2004 ; Liu Y. et al, 2011 ; Chen, 2012 ; Hao et al, 2013 ; Huang et al, 2013 ; Su et al, 2013 ; Wang and Yu, 2013 ; Li et al, 2015 ), PS with IHD (Wang et al, 2009 ; Zhao, 2009 ; Fang et al, 2011 ; Kong et al, 2014 ) and PSCS with IHD (Zhang et al, 1995 , 1999 ; Liu et al, 2008 ; Bai and Song, 2012 ; Lin et al, 2014 ; Zhao L. et al, 2014 ; Ren et al, 2015 ). However, the molecular mechanisms of PSCS with IHD have not been fully elucidated clearly and have not yet been investigated from a network medicine perspective (Hopkins, 2007 ; Li and Zhang, 2013 ), in particular the symptoms or cluster of symptoms (corresponding to specific syndromes) have been always ignored to be explored in system biology (Zhou et al, 2014a , b ), although symptoms were the most common and focused phenotypes in TCM (Chung, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phlegm and blood-stasis are regarded as the most common patterns of CAD patients [ 5 ]. They are significantly related to hyperlipidemia [ 6 ] and atherosclerosis and platelet activating system [ 7 ], which determines the prognosis and stratification of CAD. Phlegm is defined as a viscous, turbid pathological product that can accumulate in the body, causing a variety of diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%